Current Approach in the Diagnosis and Management of Allergic Bronchopulmonary Aspergillosis in Children With Cystic Fibrosis - Sunman, Birce; Ademhan Tural, Dilber; Ozsezen, Beste; Emiralioglu, Nagehan; Yalcin, Ebru; Özçelik, Uğur (Frontiers in Pediatrics, 2020)
Allergic bronchopulmonary aspergillosis (ABPA) is a complex pulmonary disorder characterized by a hypersensitivity reaction to Aspergillus fumigatus, and almost always seen in patients with cystic fibrosis (CF) and asthma. Fungal hyphae leads to an ongoing inflammation in the airways that may result in bronchiectasis, fibrosis, and eventually loss of lung function. Despite the fact that ABPA is thought to be more prevalent in CF than in asthma, the literature on ABPA in CF is more limited. The diagnosis is challenging and may be delayed because it is made based on a combination of clinical features, and radiologic and immunologic findings. With clinical deterioration of a patient with CF, ABPA is important to be kept in mind because clinical manifestations mimic pulmonary exacerbations of CF. Early diagnosis and appropriate treatment are important in preventing complications related to ABPA. Treatment modalities involve the use of anti-inflammatory agents to suppress the immune hyperreactivity and the use of antifungal agents to reduce fungal burden. Recently, in an effort to treat refractory patients or to reduce adverse effects of steroids, other treatment options such as monoclonal antibodies have started to be used. Intensive research of these new agents in the treatment of children is being conducted to address insufficient data.